Anatomical Study of Sinus Tarsi–Based Lateral Lengthening Calcaneal Osteotomy. (January 2022) - Aurich, Matthias; Lenz, Mark; Hofmann, Gunther O.; Schubert, Wiebke; Knobe, Matthias; Roth, Klaus Edgar; Simons, Paul; Klos, Kajetan
Background: Lateral lengthening calcaneal osteotomy (LL-CO) is commonly performed as a treatment for an abducted midfoot in pes planovalgus deformity. The purpose of this study is to investigate potential damage to medial structures with a sinus tarsi LL-CO. Methods: Sixteen cadaver feet were used. Eight feet had an extended lateral approach, and 8 had a limited lateral (sinus tarsi) approach. All underwent a sinus tarsi LL-CO. Specimens were then dissected to identify inadvertent injury to medial structures. Results: Sinus tarsi LL-CO was associated with damage to the sustentaculum tali and medial articular facets in 56% and 62.5% of specimens, respectively. No anterior or posterior facet injuries were found, although 56% of specimens had a confluent medial and anterior facet. Conclusion: Damage to the medial articular facet and sustentaculum is possible with a flat cut sinus tarsi LL-CO due to the curved nature of the relevant sinus tarsi and canal anatomy. Clinical Relevance: Sinus tarsi LL-CO needs to be performed with caution since damage to the subtalar joint is possible. Level of Evidence: Level II, prospective cohort study.